2016
DOI: 10.1186/s12964-016-0135-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Lyn-dependence of the SHIP1-deficient mast cell phenotype

Abstract: BackgroundAntigen (Ag)/IgE-mediated mast cell (MC) responses play detrimental roles in allergic diseases. MC activation via the high-affinity receptor for IgE (FcεRI) is controlled by the Src family kinase Lyn. Lyn-deficient (-/-) bone marrow-derived MCs (BMMCs) have been shown by various laboratories to exert stronger activation of the PI3K pathway, degranulation, and production of pro-inflammatory cytokines compared to wild-type (wt) cells. This mimics the phenotype of BMMCs deficient for the SH2-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…This indicated that effects on degranulation and Ca 2+ mobilisation were quantitatively uncoupled in DKO BMMCs. Such uncoupling has also been reported, amongst others, in Lyn -deficient as well as in Ship1/Lyn double-deficient BMMCs 27 , 28 . The exact mechanism has not been elucidated yet.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…This indicated that effects on degranulation and Ca 2+ mobilisation were quantitatively uncoupled in DKO BMMCs. Such uncoupling has also been reported, amongst others, in Lyn -deficient as well as in Ship1/Lyn double-deficient BMMCs 27 , 28 . The exact mechanism has not been elucidated yet.…”
Section: Resultssupporting
confidence: 66%
“…1b , Y-P of PLCγ1 and PLCγ2 was reduced in Btk −/− BMMCs compared to WT cells; moreover, Y-P of PLCγ1 and PLCγ2 in Ship1 −/− BMMCs was drastically augmented (Fig. 2e ) 28 . This enhancement was reduced in DKO BMMCs to Y-P levels found in WT cells (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The cytosolic phosphatase SHIP-1, SH2-containing inositol-5′-phosphatase, has critical roles in microphages, including generation of alternatively activated macrophages, 39 regulation of LPS-induced macrophage inflammatory responses 40 and modulation of myeloproliferation. 11 Diverse cellular functions have been previously investigated in association of Lyn and SHIP-1, 41 , 42 but whether Lyn is involved in SHIP-1 expression or membrane translation 43 remains unclear. To investigate it, we measured SHIP-1 expression in Lyn-silenced and control MH-S cells at 0, 30 and 60 min post infection of PAO1.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse cellular functions have been previously investigated in association with both Lyn and SHIP-1. 41 , 42 SHIP-1 and Lyn are involved in regulation of integrin alpha IIb-β3 signaling in platelets, 41 and in respect to Ag-triggered degranulation in mast cells. 42 In macrophages, Lyn and SHIP-1 negatively regulate macrophage colony-stimulating factor-induced Akt activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation